Modulating Intrafollicular Hormonal Milieu in Controlled Ovarian Stimulation: Insights From PPAR Expression in Human Granulosa Cells. Issue 4 (9th September 2015) - Tatone, Carla; Benedetti, Elisabetta; Vitti, Maurizio; Di Emidio, Giovanna; Ciriminna, Rosanna; Vento, Maria Elena; Cela, Vito; Borzì, Placido; Carta, Gaspare; Lispi, Monica; Cimini, Anna Maria; Artini, Paolo Giovanni; et al.
Abstract : Controlled ovarian stimulation (COS) leading to ovulation of multiple follicles is a crucial aspect of biomedical infertility care. Nevertheless, biomarkers useful for COS management are still lacking. Peroxisome proliferator‐activated receptors (PPARs) are nuclear hormone receptors relevant to steroid metabolism in granulosa cells (GCs). We investigated whether PPARs and their steroidogenic targets were differentially expressed in GCs differentiated under different recombinant or urinary gonadotropin preparations. GCs from women subjected to COS with r‐hFSH, r‐hFSH/r‐hLH, or hMG‐HP were processed to assess expression of PPARα, PPARβ/δ, PPARγ, and steroidogenic enzymes under PPAR modulation. As an evidence of their activation, all PPAR isotypes with their coactivators, the retinoic‐X‐receptors (RXRs), localized in the nucleus. When GCs from r‐hFSH/r‐hLH group were compared with r‐hFSH, a significant reduction of PPARα protein was observed. By contrast, an increase of PPARβ/δ at both protein and mRNA levels along with that of PPARγ protein were detected. The steroidogenic enzymes 17βHSD IV, 3βHSD II, and HMG‐CoA red were downregulated in the r‐hFSH/r‐hLH group in comparison to r‐hFSH unlike CYP19A1 that remained unchanged. In GCs from urinary FSH‐LH stimulation (hMG‐HP), PPARα was more expressed in comparison with r‐hFSH/r‐hLH group. Likewise, 3βHSD II and 17βHSD IV were increased suggesting that hMG‐HP partially mimicked r‐hFSH/r‐hLH effects. In summary, transcript analysis associated to protein investigation revealed differential effects of COS protocols on PPARs and their steroidogenic targets in relation to LH and gonadotropin source. These observations candidate PPARs as new biomarkers of follicle competence opening new hypotheses on COS effects on ovarian physiology. J. Cell. Physiol. 231: 908–914, 2016. © 2015 Wiley Periodicals, Inc.